Biomedical materials and diagnostic devices - Tiwari, Ashutosh, 1978- (John Wiley & Sons ; Scrivener Pub., 2012)
The functional materials with the most promising outlook have the ability to precisely adjust the biological phenomenon in a controlled mode. Engineering of advanced bio- materials has found striking applications in used for biomedical and diagnostic device applications, such as cell separation, stem-cell, drug delivery, hyperthermia, automated DNA extraction, gene targeting, resonance imaging, biosensors, tissue engineering and organ regeneration.